Hypertrophic Cardiomyopathy with Intermittent Free Mitral Regurgitation–A Surgical Dilemma. Issue 4 (22nd January 2014) - Gibson, Patrick H.; Khandekar, Sayra A.; Taylor, Dylan; Becher, Harald
Mini‐Abstract This report describes the case of a 52‐year‐old woman demonstrating reversible free mitral regurgitation and severe left ventricular outflow tract obstruction in the context of hypertrophic cardiomyopathy and anterior myocardial infarction. The report includes relevant 2D and 3D transthoracic and transesophageal echocardiographic images, with discussion of the possible mechanisms involved.